Oregano dietary supplementation modifies the liver transcriptome profile in broilers: RNASeq analysis. (April 2018) - Sabino, Marcella; Capomaccio, Stefano; Cappelli, Katia; Verini-Supplizi, Andrea; Bomba, Lorenzo; Ajmone-Marsan, Paolo; Cobellis, Gabriella; Olivieri, Oliviero; Pieramati, Camillo; Trabalza-Marinucci, Massimo
Abstract: Intensive farming of broilers involves stressful conditions that reduce animal welfare and performance. New dietary strategies to improve performance and meat quality include the administration of plant extracts. Oregano ( Origanum vulgare L . ) is known for its antimicrobial, anti-fungal, insecticidal and antioxidant properties. However, studies on diet supplementation with oregano are mainly focused on the evaluation of animal performance, while partial information is available on transcriptomics and nutrigenomics and, in particular, Next Generation Sequencing (NGS) is not widely applied. In this study we tested the effect of an oregano aqueous extract supplemented diet on gene expression in broiler chickens. Whole liver transcriptome of 10 birds fed with a supplemented diet versus 10 controls was analyzed using the RNA-Seq technique. One hundred and twenty-nine genes were differentially expressed with an absolute log fold change > 1. The analysis reveals a massive down-regulation of genes involved in fatty acid metabolism and insulin signaling pathways in broilers fed with the oregano aqueous extract supplementation. Down-regulated genes could be associated to chicken lean line, suggesting the potential beneficial effect of oregano supplementation in reducing both abdominal and visceral fat deposition. Down-regulation of insulin signaling pathway related genes suggest that dietary oregano supplementation might be an option in obesity and diabetes conditions. Highlights: RNA-Seq reveals that oregano modulates liver transcriptome expression. Fat metabolism and pathways are down regulated. Insights on the molecular basis of lean body mass and visceral fat are speculated.